On the effect of pitch and yaw angles in oblique impacts of small-caliber projectiles - Teresa Fras (Defence Technology, 2024)
A terminal ballistic analysis of the effects of 7.62 mm × 51 AP P80 rounds on inclined high-strength armor steel plates is the focus of the presented study. The findings of an instrumented ballistic testing combined with 3D advanced numerical simulations performed using the IMPETUS Afea® software yielded the conclusions. The experimental verification proved that slight differences in the pitch-and-yaw angles of a projectile upon an impact caused different damage types to the projectile’s core. The residual velocities predicted numerically were close to the experimental values and the calculated core deviations were in satisfactory agreement with the experimental results. An extended matrix of the core deviation angles with combinations of pitch-and-yaw upon impact angles was subsequently built on the basis of the numerical study. The presented experimental and numerical investigation examined thoroughly the influence of the initial pitch and yaw angles on the after-perforation projectile’s performance.